2013
DOI: 10.1093/annonc/mdt071
|View full text |Cite
|
Sign up to set email alerts
|

ROS1 fusions in Chinese patients with non-small-cell lung cancer

Abstract: ROS1 fusions occurred in ∼2.0% of Chinese patients with NSCLC and had no specific clinicopathological feature. ROS1 fusion-negative patients may have a better survival than ROS1 fusion-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 26 publications
11
69
4
Order By: Relevance
“…30,37 However, this association has not been consistently observed across studies. 34 Other clinical characteristics, such as younger age, female sex, and non-Asian ethnicity, have been associated with ROS1 rearrangement in isolated studies only. 30,31,35 Therefore, clinical characteristics should not be used to either select or exclude patients from testing for ROS1 rearrangements.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
See 2 more Smart Citations
“…30,37 However, this association has not been consistently observed across studies. 34 Other clinical characteristics, such as younger age, female sex, and non-Asian ethnicity, have been associated with ROS1 rearrangement in isolated studies only. 30,31,35 Therefore, clinical characteristics should not be used to either select or exclude patients from testing for ROS1 rearrangements.…”
Section: Expert Consensus Opinionmentioning
confidence: 99%
“…This recommendation is evidence based and supported by 9 studies, 30e38 6 of which informed on the association between ROS1 rearrangement and patient or tumor characteristics 30,31,34e37 and consisted of 1 prospective cohort study (PCS), 35 1 prospective-retrospective cohort study (PRCS), 31 and 4 retrospective cohort studies (RCSs). 30,34,36,37 The 3 remaining studies assessed clinical outcomes of patients treated with the ROS1-targeted therapy crizotinib 32,33,38 and included 1 nonrandomized clinical trial 33 and 3 RCSs. 32,38 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' findings (SDC Table 6).…”
Section: Strong Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS1 fusions are widespread in never-smokers with a histological diagnosis of adenocarcinoma (54). In patients with NSCLC, chromosomal translocations have been identified by ROS1-solute carrier family 34 member 2 (SLC34A2) and ROS1-cluster of differentiation 74 (CD74) fusions, which involve the fusion of the 5' region of SLC34A2 with the 3' region of ROS1 and the fusion of the 5' region of CD74 with the 3' region of ROS1, respectively (55).…”
Section: Molecular Biology Of Lung Cancermentioning
confidence: 99%
“…Such rearrangements have been identified in approximately 1%–2% of NSCLC patients using different genotyping techniques (Table 3). 47,48 Several recent studies used whole-transcriptome and whole-genome sequencing to detect ROS1 rearrangements, and several novel fusion partners were identified 47,48. Such methods are not yet readily applicable in the clinic.…”
Section: Prevalence Of Driver Mutations In Lung Cancersmentioning
confidence: 99%